Socioeconomic Analysis of Octopus Handline Fishers in Aceh Besar - Nurhayati Nurhayati; Alvi Rahmah; Ahmad Fauzan Lubis; Imelda Agustina; Inda Mardhatillah; Khairatun Safrita; Ricky Winrison Fuah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
This study examines the social and economic conditions of octopus handline fishers in Gampong Lamteungoh, Aceh Besar. The research was motivated by declining catch production, which potentially affects fishers’ household welfare. The study aims to describe social conditions and analyze economic conditions based on income levels. Data were collected in April 2025 using a census method involving 30 fishers through observation, interviews, and documentation. Social conditions were analyzed descriptively using welfare indicators from Statistics Indonesia (BPS), while economic conditions were analyzed using income analysis. The results show that 97% of fishers have high social welfare and 3% moderate welfare, based on housing, education, and access to basic services. However, economically, fishers remain vulnerable, with an average income of IDR 1,909,365 per month, which is below the regional minimum wage. High household expenditures and declining catches contribute to this condition. The study highlights the need for improved fisheries management and economic support for small scale fishers.